English: English - Polish, Polish; Polish, Polish; Ćwiklińska, Agnieszka (Journal of Medical Biochemistry, 2023)
The pre-analytical phase is the principal source of errors in laboratory medicine and continues to pose a challenge to laboratory professionals. We present the case of a 73-year-old female patient with a very low haemoglobin level (69 g/L) and positive indirect antiglobulin test result that indicates the key role of phlebotomy as an important error-prone process in which mistakes can have serious consequences for the patient’s diagnosis and treatment. We conclude that there is still an urgent and continuous need to provide educational activities for healthcare professionals involved in blood collection, improve blood collection guideline adherence, and eliminate the errors which can affect diagnosis and treatment, thus jeopardising patient safety.
Keywords: English